Congenital Diaphragmatic Hernia: Antenatal Diagnosis and Successful Repair In Preterm Neonate Case Report - Al-Fadhli, Wasmi; Al-Munaifi, Sulaiman; Abdelazim, Ibrahim A. (Gynecology Obstetrics & Reproductive Medicine, 2018)
Most of the congenital diaphragmatic hernias (CDH) observed in the left hemi diaphragm. The pathogenesis of CDH is not completely understood; but abnormal development of the diaphragm at 6-10 weeks' supposed to be the cause in most of the cases. Although CDH usually occurs sporadically, environmental exposures have been implicated. Improvement of the antenatal imaging techniques has allowed early diagnosis and evaluation of the associated anomalies. In antenatally diagnosed CDH cases, multidisciplinary team management and delivery at tertiary centers with proper facilities may be provided to optimize the outcome. A 39-year-old woman, with the history of one previous cesarean section, was admitted to the hospital at 25 weeks’ gestation, because of placenta previa and her antenatal ultrasound showed fetal CDH with polyhydramnios. During hospitalization, she was monitored for hemoglobin levels, consumptive coagulopathy, and fetal well-being. Betamethasone was given to accelerate the fetal lung maturity, and magnesium sulphate for fetal neuro-protection. Due to an attack of heavy antepartum hemorrhage, delivery occurred at the gestational age of 28 weeks + 6 days. The delivered female newborn was admitted to the neonatal intensive care unit (NICU) because of respiratory distress and prematurity, and received surfactant, dobutamine and intravenous antibiotics. Chest examination of the studied neonate showed diminished air entry on the left side, and chest X-ray showed stomach shadow in the left hemi thorax. After exclusion of congenital heart diseases and intracranial hemorrhage, the baby was successfully operated on the postpartum 7th day, and discharged from the NICU 60 days after the operation. Two months after discharge from the NICU, examination of the studied neonate was successfully operated on the postpartum 7th day showed normal growth parameters and appropriate motor and sensory development for her age. Antenatal diagnosis of CDH allows multidisciplinary team management and delivery at tertiary center with the proper facilities to optimize the outcome.